Little dog, lost - Bauer, Marion Dane (Atheneum Books for Young Readers, 2012)
A boy, a dog, and an old man are lonely before the boy plans a rally, the dog looks for a boy, and all the townspeople run to the old man's aid when lightning strikes his home and something miraculous happens.